Legal Protection for Parties in Transferring Receivables from Factoring Transactions (Factoring) - Shohib Muslim (Universitas Airlangga, 2022)
An agreement can be born not enough just by the will; the will is not stated according to the theory of statements (verklaring theory). Furthermore, according to the theory of trust (vertrouwens theory), it is argued that the stated will becomes an agreement that can produce an agreement. We attempted to identify the existence of an agreement factoring and transfer of receivables in the practice of factoring transactions that have provided legal protection to the parties in the perspective of consumer protection and the principle of freedom of contract. Here, we conducted a legal analysis on certain legal phenomena in Indonesia related to factoring transaction. The scope of this study was limited to factoring activities of a financing nature, particularly related to the purchase and transfer of receivables in factoring transactions in Indonesia (domestic factoring). Philosophical issues related to factoring transactions, where factoring is an institution adopted from the British legal system and the American legal system (common law), influenced by the understanding and principles of materialism, individualism and liberalism, while the Indonesian legal system is based on Pancasila, based on the principles of God, kinship, togetherness and mutual cooperation, balance, and responsible freedom. In our analysis, we found that the process of making the agreement is prepared and determined unilaterally by the factor by providing a very minimal portion for the client to negotiate. Thus, the factoring agreement does not fulfill the principle of balance and the principle of freedom of contract.